Academia journal of biology Volume 42, Number 3 (H. Vietnam academy of science and technology, 2020)
Contents:Cyperus entrerianus Boeckeler, a new record from Vietnam;New records of the genus Miconchus (Mononchida, Anatonchidae) for Vietnam nematode fauna; Multi-correlation between nematode communities and environmental variables in mangrove-shrimp ponds, Ca Mau Province, Southern Vietnam;...
Formerly Tạp chí sinh học (Journal of Biology)
Keywords: Tạp chí